PRESIDENT SUSILO BAMBANG YUDHOYONO ADMINISTRATION GOVERNMENT PERFORMANCE MEASUREMENT IN 2004-2009 PERIOD USING A BALANCE SCORECARD APPROACH - Mohammad Abdul Mukhyi (Universitas Gunadarma, 2009)
Balance Scorecard is a management performance analysis technique designed to translate an organization's mission statement and overall business strategy into specific, quantifiable goals and to monitor the organization's performance in terms of achieving these goals developed by Kaplan and Norton. Balance scorecard was originally created to overcome the problem associated with management performance measurement system which focuses limitedly on financial aspects. It is a comprehensive approach that analyzes an organization's overall performance in four ways: financial analysis, customer analysis, internal analysis, and learning and growth analysis. In addition, it is designed to translate an organization's mission statement and overall business strategy into specific, quantifiable goals and to monitor the organization's performance in terms of achieving these goals.Balanced Scorecard development experience in the implementation, not only used to measure the performance of the company but will also be applied to measure the performance of government. Research purposes to measure management performance of the SBYJK administration from both financial and non financial perspectives. It was concluded that from the financial perspective, the administration has achieved satisfactory results; from customer (stakeholder), internal business, and learning and growth perspectives the administration has also achieved results which were satisfactory.This means that performance of the overall SBY-JK administrations was satisfactory.Keywords: balance scorecard, financial performance; customer (stakeholder); internal business process; learning and growth processes.